AN ANALYSIS OF BILINGUAL LEARNING ON LANGUAGE DEVELOPMENT AT TUNAS MELATI KINDERGARTEN - Khoirunnisa; Meri Hartati; Melli Kusmaningrum; Masita Arianie; Rizki Yunita Putri (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study aims to analyze the implementation of bilingual learning in the language development of early childhood students at Tunas Melati Kindergarten. The results of the study show that a bilingual program that is implemented consistently and innovatively, using additive methods and supported by interactive play activities, can improve children's linguistic abilities, such as vocabulary acquisition, understanding of instructions, and confidence in speaking English. Moreover, this approach also strengthens the holistic development of children through a fun, natural, and developmentally appropriate learning processes during the “golden age” phase. The concepts of scaffolding and social interaction principles also play a role in the success of this program, thereby supporting children's readiness to face the demands of the curriculum and globalization. Thus, the proper implementation of bilingual learning can provide long-term benefits in language proficiency and academic readiness for early childhood